2017
DOI: 10.1016/j.fertnstert.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcome and information on fertility issues in individuals with different forms of disorders of sex development: findings from the dsd-LIFE study

Abstract: Fertility outcome is significantly reduced in all types of DSD; however, fertility potential should be assessed individually. The satisfaction with how fertility problems have been discussed can be improved. The care of patients with DSD is complex, should be individualized, and new treatment possibilities incorporated. A close collaboration in multidisciplinary teams is therefore essential to improve the situation for individuals with DSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…There were also women in the Turner group, younger than 50 years of age, who had not had any HRT, some of whom had menstruations. Also, for this group, it is likely that mosaicism had resulted in some endogenous hormone production, and as reported previously, 5 women in this Turner group had children without ART …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There were also women in the Turner group, younger than 50 years of age, who had not had any HRT, some of whom had menstruations. Also, for this group, it is likely that mosaicism had resulted in some endogenous hormone production, and as reported previously, 5 women in this Turner group had children without ART …”
Section: Discussionsupporting
confidence: 67%
“…The reason that the other 36 did not have HRT is not known, but it can be speculated that at least some individuals in the Klinefelter group may have sufficient endogenous testosterone production . We have reported previously that there were 2 individuals with Klinefelter reporting to have a biological child without ART which speaks in favour of a situation with mosaicism resulting in sufficient testis function . There were also women in the Turner group, younger than 50 years of age, who had not had any HRT, some of whom had menstruations.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that 55% of patients who thought they were unable to have biological children expressed a desire to have had fertility treatment in the past or have it in the future. In addition, 40% indicated that they would like to try new techniques for fertility treatment in the future …”
Section: Preservation Of Biological Fertility Potentialmentioning
confidence: 99%
“…In addition, 40% indicated that they would like to try new techniques for fertility treatment in the future. 53 Fertility preservation has been driven predominantly by oncofertility which is a field dedicated to preserving the fertility of patients undergoing gonadotoxic cancer treatment. As there is growing evidence of individuals with DSD wishing to retain the potential for biological fertility, 2,53 the use of fertility preservation techniques could, and should, be expanded to include this group.…”
Section: Pre S Ervati On Of B I Olog I C Al Fertilit Y P Otentialmentioning
confidence: 99%
“…Others are notmay be infertile; however, their gonads -whether ovaries or testes -are capable of producing hormones. There are also some intersex people who, while not capable of unassisted reproduction, may be able to have children with medical support, either with currently available assisted reproductive technologies (ART) [35] or as new scientific advances occur. Those with functioning ovaries but no uterus may opt for surrogacy [2].…”
Section: Fertility In Intersex Peoplementioning
confidence: 99%